Inductive Bible Study: Contextual Appropriation in Northeast India - Jamir, M. (The Asbury journal, 2013)
M. Sashi Jamir examines the application of Inductive Bible Study to the tribal communities of Northeast India. This postcolonial situation has some positives such as a context with a higher degree of education, but it has also lead to a prominence of Western philosophy over traditional ways of understanding, which need to be reclaimed. The reality that larger national forces in India often overshadow tribal communities also poses potential problems that prevent the local theological voice from being heard.